Website Development as a Media for Disseminating Information in RT. 39 Jelutung Village, Jambi City - Ikhsan, Muhammad; Darmuji, Darmuji; Adhiatma, Novri; Helmina, Helmina (Yayasan Cita Cendekiawan Al Khwarizmi, 2024)
RT 39 Jelutung Village, Jambi City is currently facing challenges in terms of disseminating information to its citizens. Conventional methods that have been used, such as announcements on information boards, regular meetings, and distributing leaflets, are often ineffective in reaching all residents. This research seeks to create a website for sharing information for disseminating information in RT. 39, Jelutung Village, Jambi City, using the Waterfall method and UML modeling to describe the system flow. This website is designed to facilitate effective communication between RT administrators and residents and provide fast and accurate access to information regarding activities, announcements and public services. The Waterfall methodology includes the phases of needs analysis, design, implementation, testing and maintenance. UML modeling is used to visually describe the structure and flow of a system, including use case diagrams, activity diagrams, and class diagrams. The finding is a website with main features such as Information Portal, Website Dashboard, Manage Mail. Evaluation was carried out through a survey of RT residents. 39 to assess the effectiveness and satisfaction with the use of this website. The evaluation results show that this website has succeeded in increasing information accessibility and citizen participation in RT activities. 39. Thus, it is hoped that the development of this website can become a model that can be applied in other RTs To enhance the caliber of communication and informational offerings.